A Robust Receding-Horizon Collision Avoidance Strategy for Constrained Unmanned Ground Vehicles Moving in Shared Planar Environments - Savehshemshaki, Shima; Lucia, Walter (Proceedings of the IEEE Conference on Decision & Control, 2022)
This paper deals with the reference tracking and collision avoidance control problems for constrained unmanned ground vehicles moving in shared planar environments. The proposed solution improves the strategy developed in [1] by minimizing the number of vehicle's full stops required to avoid collisions. This is achieved through a modified traffic manager algorithm that can exploit, in a receding horizon fashion, a preview of the successive vehicle's waypoints. Such information is properly used to speed up or speed down the vehicles and minimize the chances of future collisions and vehicle's full stops. The proposed control solutions enjoys recursive feasibility regardless of the waypoint prediction horizon.